Asymmetry in the ERM : A Case Study of French and German Interest Rates Since Basle-Nyborg - Perraudin, W. (IMF Working Papers; Working Paper ;, 1992)
We study empirically daily French and German interest rate changes since the Basle-Nyborg agreement of September 1987. In particular, we ask whether the shock associated with German unification altered the degree of leadership of German monetary policy in the ERM. We conclude that Germany's leadership role within the ERM largely disappeared in the year following unification but that the Bundesbank has recently begun to reassert its predominance.